EFEKTIVITAS APLIKASI SIMAK DIHATI SEBAGAI REALISASI ABSENSI ONLINE BERBASIS ELEKTRONIK DALAM MENINGKATKAN DISIPLIN PEGAWAI : (Studi Kasus: Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kota Denpasar) - Ni Luh Gede Diandra Adi Pradnyaswari; Juwita Pratiwi Lukman; I Dewa Ayu Putri Wirantari (Triwikrama: Jurnal Ilmu Sosial, 2025)
This research aims to find out how effective the Simak Dihati application is in improving employee discipline at BKPSDM Denpasar City, where in its implementation since 2023 several problems were still found, such as the application frequently having errors, difficulty accessing because the internet network was weak, and the lack of employee awareness of taking attendance on time. This research aims to determine the effectiveness of the Simak Dihati application in improving employee discipline at BKPSDM Denpasar City. The method used in this research is a qualitative research method with data collection techniques in the form of interviews, observation and documentation. This research uses effectiveness indicators according to Duncan in Kharisma which consist of Goal Achievement, Integration and Adaptation. The research results show that the implementation of attendance through the Simak Dihati application has been effective but not completely optimal. In term from the indicators for achieving goals, integration and adaptation have been running quite effectively, but still do not meet the adaptation indicators because there are still employees who lack awareness of being able to make absences, one of which is because they forget to be absent as well as facilities and infrastructure where applications still experience errors and signal coverage quality is less stable. The recommendations from this research are to carry out further monitoring in monitoring employee absenteeism, increase in quantity of WiFi in BKPSDM Denpasar City, establishing special or official sanctions for non-ASN employees and making improvements to the Simak Dihati application so that it causes minimal problems in its use.